Sliding Humeral Osteotomy: Medium‐Term Objective Outcome Measures and Reduction of Complications With a Modified Technique. Issue 2 (30th September 2014) - Fitzpatrick, Noel; Bertran, Judith; Solano, Miguel A.
<x xml:space="preserve">Abstract</x> Objective To determine mid‐term complication rate associated with a modified sliding humeral osteotomy (SHO) technique and compare clinical outcome with or without focal treatment (FT). Animals Dogs (n = 46; 60 elbows) with severe or persistent lameness attributable to medial coronoid disease (MCD). Methods Signalment, lameness, pain score, and preoperative radiographic findings were recorded. Modified Outerbridge score and fissure/fragmentation were recorded arthroscopically. SHO was performed with technical modifications. Outcome measures included lameness score, elbow pain score, owner function assessment, and force‐plate preoperatively, at 6 and 12 weeks, and 6–25 months. Results SHO was performed on 60 limbs; 22 also had FT of the medial coronoid process. Mean (±SD) dog age was 44.17 ± 33.0 months and weight range was 17.4–49.8 kg. Preoperative duration of lameness was 2.16 ± 0.69 months. Lameness improved for all limbs by 12 weeks, and resolved in 49 limbs. Significant improvements in postoperative pain scores and most owner function assessments occurred. There was no significant difference with or without FT. There were no major complications and 4.17% minor complications. Force‐plate data available for 18 of 46 dogs operated unilaterally preoperatively and at last follow‐up showed significant improvement in ground reaction force and reduction of asymmetry index (t‐test; P < .05). Conclusions SHO with or without focal treatment of the medial aspect of the coronoid process ameliorates lameness and pain associated with MCD at medium‐term follow‐up. Application technique is critical to minimize morbidity.